Mindfulness-based cognitive therapy improves insomnia symptoms in individuals with recurrent depression: secondary analyses from a randomized controlled trial - Evanger, Linn Nyjordet; Flo-Groeneboom, Elisabeth; Sørensen, Lin; Schanche, Elisabeth (Frontiers in Psychiatry, 2024)
Background Embedded within a randomized efficacy trial, the present study aimed to investigate whether mindfulness-based cognitive therapy (MBCT) for recurrent depression improved symptoms of insomnia. Methods Sixty-eight remitted participants with at least three prior episodes of depression were randomized to 8 weeks of MBCT (n = 33) or a waitlist control condition (n = 35). The Bergen Insomnia Scale was used to screen for insomnia symptoms before and after the intervention. The analyses were conducted using one-way between-groups analyses of covariance. Results Twenty-five MBCT participants and 30 waitlist controls completed the study (74.5% females; mean age 40.7 ± 12.9 years). At baseline, 83.6% screened positive for the insomnia diagnosis. Following the intervention and after controlling for corresponding insomnia parameters at baseline, MBCT completers reported significantly less severe insomnia symptoms (p = 0.017), as well as less problems with prolonged sleep onset (p = 0.047) and nocturnal awakenings (p = 0.023), relative to controls. No group differences were found on early morning awakening, daytime impairment, or dissatisfaction with sleep. Conclusion The results suggest that MBCT improves certain insomnia symptoms. However, additional sleep-specific interventions may be needed to further improve this population’s sleep. Clinical Trial Registration: ISRCTN, ISRCTN18001392, registered 22/11/2018. URL: 10.1186/ISRCTN18001392.